Thermally activated delayed fluorescent (TADF) coordination polymer with the generation of singlet oxygen. Issue 6 (23rd May 2019) - Ren, Xiu-Hui; Li, Gang-Yuan; Du, Hua; Ma, Jian-Ping; Geng, Yan; Dong, Yu-bin
Abstract : 4, 4′‐9, 9′‐Spirobi[10 H ‐acridine]‐10, 10′‐diyldibenzoic acid was designed and synthesized as a new donor–acceptor motif molecule and applied as a ligand with Cd as a metal connector to form a one‐dimensional coordination polymer. Both the ligand and the polymer present a sky‐blue TADF emission, together with a photoluminescence quantum yield of 40%. Abstract : 4, 4′‐9, 9′‐Spirobi[10 H ‐acridine]‐10, 10′‐diyldibenzoic acid (L, C29 H26 N2 O4 ) was designed and synthesized as a new donor–acceptor motif molecule. Due to the large dihedral angle between the planes of the carboxyphenyl group and the spiroacridine moiety, L possess thermally activated delayed fluorescence (TADF). By applyingL as a ligand and using Cd as a metal connector, we synthesized the coordination polymer catena ‐poly[hemi‐μ‐aqua‐aqua(μ3 ‐4, 4′‐9, 9′‐spirobi[10 H ‐acridine]‐10, 10′‐diyldibenzoato)cadmium(II)], [Cd(C29 H24 N2 O4 )(H2 O)1.5 ] n, (I ). X‐ray crystallographic analysis revealed that this coordination polymer exhibits one‐dimensional chains constructed from molecular twist‐ring moieties, with Cd2 O11 clusters as the connection nodes. The stacking pattern of the two‐dimensional network was formed by C—H…π interactions in the solid state. Similar toL, (I ) presents a sky‐blue TADF emission, together with a photoluminescence quantum yield (PLQY) of 40%. It is worth noting that the photocatalytic activity toward the generation of singlet oxygen of this coordination polymer is confirmed.